Biobank in Peninsular Malaysia: challenges and concerns - Yaakob, Adzidah; Mustafa, Maizatun; Zakaria, Mohamad Zaharuddin; Imam Supaat, Dina; Wook, Izawati; Mahzir, Nurulnadiah (2017)
Forested areas in Peninsular Malaysia have been reduced over the years and continue to decline even now. Despite the need for development, it is indeed a need to sustain and conserve our forest biodiversity in order to prevent it from disappearing hence, jeopardizing the rights of future generation. The establishment of biobank in Malua Wildlife Habitat Conservation Bank (MWHCB) of Sabah is seen significant in protecting and sustaining forest for its species and for habitat of wild life. Thus, this paper intends to discuss the challenges and concerns of establishing biobank in Peninsular Malaysia for instances location of biobank forested area; biobank operational financing mechanism; social acceptance and other related issues. This study emphasizes on qualitative approach using analytical and comparative methods on the practices of bio bank in Sabah. It is a doctrinal library-based study on the Malaysian case laws, as well as literature and academic texts on biobank and forest conservation in Peninsular Malaysia, East Malaysia, Sabah and international practices. Thus, the establishment of biobank for forest protection is seen significant in assuring the existence of forest species, flora and fauna inasmuch as reduces the impact of global warming